The African Informal Economy - Omobowale, Ayokunle Olumuyiwa (Social Sciences E-Books Online, Collection 2024., 2024)
The informal sector is a vital sustainer of the African economy, employing more than 60% of sub-Saharan Africans. The book examines diverse segments of the informal sector, putting into consideration their structure, dynamics, resilience and gender issues. Chapters are based on empirical research on women in the transport sector, vehicle maintenance artisanship, graduates in the informal sector, COVID 19, and the informal economy. Other chapters focus on the indigenous usury finance system, coconut oil production, herbal medicine, and the gig economy across countries including Nigeria, Kenya, Ghana, Togo, and Burkina Faso.